2014
DOI: 10.5603/kp.a2014.0114
|View full text |Cite
|
Sign up to set email alerts
|

Impact of serum alkaline phosphatase level on coronary collateral circulation

Abstract: Serum ALP is a widely avaliable unfavourable prognostic parameter in coronary heart disease. Elevated ALP levels were associated with inadequate CCC, which supports the previously reported literature concerning the negative prognostic value of ALP levels in cardiovascular settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…A more recent report by Perticone and colleagues described a significant inverse relationship between TNAP and endothelium-dependent vasodilation, 15 and Karabulut and coworkers reported that TNAP levels are associated with an inadequate coronary collateral circulation. 16 Although the studies cited above suggest a role for TNAP in the vasculature, whether TNAP actually regulates vascular responses to vasoconstrictors is an open, and important, question.…”
Section: Introductionmentioning
confidence: 99%
“…A more recent report by Perticone and colleagues described a significant inverse relationship between TNAP and endothelium-dependent vasodilation, 15 and Karabulut and coworkers reported that TNAP levels are associated with an inadequate coronary collateral circulation. 16 Although the studies cited above suggest a role for TNAP in the vasculature, whether TNAP actually regulates vascular responses to vasoconstrictors is an open, and important, question.…”
Section: Introductionmentioning
confidence: 99%
“…58 High ALP concentrations predicted lack of coronary collateral circulation, isolating a population particularly vulnerable to complications of MI. 56 Apart from the general population of patients with MI, ALP and OPN can be used for stratification of critical, high-risk subgroups. Alkaline phosphatase, in synergy with the GFR, could predict survival in male patients with diabetes after MI.…”
Section: Alkaline Phosphatasementioning
confidence: 99%
“…58 High ALP concentrations predicted lack of coronary collateral circulation, isolating a population particularly vulnerable to complications of MI. 56…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal AP has been associated with many of the risk factors leading to stroke, including heavy drinking (Ebuehi and Asonye 2007;Shimizu et al 2013a), obesity (Menahan et al 1985;Golik et al 1991), and hypertension (Shimizu et al 2013b). Elevated AP has been shown to correlate with poor functional outcome and mortality in cardiovascular disease (Park et al 2013;Wannamethee et al 2013;Karabulut et al 2014;Kunutsor et al 2014) and in stroke patients (Ryu et al 2010;Kim et al 2013;Tan et al 2016). Investigators theorize that the negative association between AP levels and stroke outcome may be linked to the fact that increased AP levels are associated with increased inflammation and enhanced vascular calcification leading to atherosclerosis (Tonelli et al 2009;Kim et al 2013;Ryu et al 2014).…”
Section: Alkaline Phosphatase As a Diagnostic And Prognostic Stroke Biomarkermentioning
confidence: 99%